2013
DOI: 10.1371/journal.pone.0062530
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearities Lead to Qualitative Differences in Population Dynamics of Predator-Prey Systems

Abstract: Since typically there are many predators feeding on most herbivores in natural communities, understanding multiple predator effects is critical for both community and applied ecology. Experiments of multiple predator effects on prey populations are extremely demanding, as the number of treatments and the amount of labour associated with these experiments increases exponentially with the number of species in question. Therefore, researchers tend to vary only presence/absence of the species and use only one (sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…These models have demonstrated that natural enemy activity sometimes causes significant declines in pest densities [ 63 ]. However, as the number of variables increases, especially with respect to natural enemy species interacting with the pest, resulting population dynamics are complicated owing to non-linear effects (e.g., natural enemy behaviors) and model outcomes may be sensitive to initial starting population densities [ 64 ].…”
Section: Pre-introduction Research On Biological Control Agentsmentioning
confidence: 99%
“…These models have demonstrated that natural enemy activity sometimes causes significant declines in pest densities [ 63 ]. However, as the number of variables increases, especially with respect to natural enemy species interacting with the pest, resulting population dynamics are complicated owing to non-linear effects (e.g., natural enemy behaviors) and model outcomes may be sensitive to initial starting population densities [ 64 ].…”
Section: Pre-introduction Research On Biological Control Agentsmentioning
confidence: 99%
“…These results suggest that increasing enemy biodiversity and whitefly control in tomatoes can be compatible and related goals [66]. At the same time, it must be acknowledged that interaction strength between natural enemies may greatly vary in different contexts (e.g., [24]). In fact, the net result of the interaction between natural enemies and prey in agroecosystems has always some level of uncertainty and context dependence.…”
Section: Enemy Biodiversity and Whiteflymentioning
confidence: 83%
“…With respect to the role of natural enemy biodiversity on pest control, biodiversity and ecosystem function studies typically explore the extent to which prey suppression is affected by variation of enemy biodiversity [4][5][6][7][8][9][10]. In fact, different aspects of enemy biodiversity including species identity [11][12][13][14], complementary prey use [6,[15][16][17], behavioural and ecological interactions between predators [18][19][20][21][22], and abundance [10,23,24] can determine emergent effects of enemy biodiversity on prey. Moreover, it is also becoming increasingly evident that emergent properties of enemy communities are context dependent and often arise from several simultaneous mechanisms that individually might produce linear or nonlinear, negative, null, and positive effects on prey suppression [5,8,9,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One S. cameroni mated female was initially used per density. Nevertheless, to prevent the results from being affected by the initial densities of the involved species – probably due to non‐linearities in the system (Ameixa et al, ) – we repeated the experiment with three times larger initial numbers of hosts and parasitoids, thus, keeping constant their relative densities, although varying their absolute densities. Translucent plastic boxes (20 cm × 15 cm × 10 cm), closed with a tight‐fitting lid that had a 4‐cm diameter gauze‐covered hole for ventilation, were used as experimental units.…”
Section: Methodsmentioning
confidence: 99%